PENGARUH PEMBERIAN ACTIVE LOWER ROM TERHADAP PERUBAHAN NILAI ANKLE BRACHIAL INDEX PASIEN DM TIPE 2 - Putu Weda Suari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Diabetes Mellitus (DM) is a metabolic disease characterized by high blood glucose levels (hyperglycemia). One of the complications of diabetes is diabetic foot. Foot problems caused by reduced peripheral blood circulation as a result of prolonged hyperglycemia conditions. An exercises that can maintain peripheral circulation of patients with type 2 diabetes is Active Lower ROM. Active lower ROM was carried out by the patient in the morning and evening, 6 days a week, for 4 weeks 10 times for each motion. The purpose of this study was to identify the effect of active lower ROM on Ankle Brachial Index (ABI) in patients type 2 of Diabetes. This research used quasi experimental design pre test and post test with control group approach which consists of 2 groups : control group and intervention group with 15 samples in each groups using purposive sampling technique. The data was collected by measuring blood pressure at the brachial and ankle regions using a sphygmomanometer. Based on the analysis results of the dependent sample t-test the control and treatment groups showed diversification between pretest and posttest value with significance value 0,429 and 0,000. Independent sample t-test of control and intervention groups showed the diversification of control and intervention group with significance value 0,002, meaning that, there were effects of the active lower ROM on Ankle Brachial Index patients with type 2 diabetes